New Normal: Learning from Home, the Availability of Information Technology and e-Learning Implementation as a Determinant of Accounting Students’ Understanding - Mochammad Ilyas Junjunan; Ajeng Tita Nawangsari; Nur Ravita Hanun (Universitas Pendidikan Ganesha, 2021)
This study aims to examines the mediating role of learning from home and the availability of information technology on the relationship between e-learning and accounting students’ understanding during the COVID 19 Pandemic. The sample of this study consist of 413 respondents from 14 universities in Indonesia. The result of the study indicate that during the COVID 19 Pandemic, learning from home and availability of information technology were able to mediate the relationship between e-learning and accounting students’ understanding in Indonesia. This study contributes in expanding the technology acceptance model theory in the context of COVID 19, and adding to the topics and theoretical approaches recommended by forum in the fields of accounting and education. It is also evaluating universities performance in implementing e-learning during COVID 19 Pandemic.